Tethering world : poems - Rambo, Jody (Wick poetry chapbook series ;, 2014)
"Jody Rambo's poems push and pull, travel and rest, occupy and set free. Her 'tether' both holds her fast to the facts and words that make up our world, but at the same time it liberates her to roam and travel, inclined as she says, 'to wander off into the green beyond recoverable limits.' What I admire most about this book is the way the wide arc of history and narrative and the smallest gesture of image and word come together--tethered--into something wondrous and new."--Jeffrey Thomson"Jody Rambo's first book of poetry, Tethering World, is lyrical, tactile, and transcendent--in a word, enthralling. The very texture embodies a personal way of seeing and saying, as does the extraordinary range of circumstances. There is a beguiling strangeness to the writing, and philosophical smarts to boot. 'I am weatherly, ' says the speaker in Tethering World, and she truly is, singularly so. This book is poetry top to bottom."--Marvin Bell"Pitched between Emily Dickinson's 'Dare you see a Soul at the White Heat?' and William Blake's 'I want! I want!, ' Jody Rambo's Tethering World offers an elegant, somatic pastoral, a 'weatherly' sensibility that forges the post-Lapsarian realm of loss and desire into an alchemical mix of rue, awe, beauty, and change--what John Keats called a 'vale of soul-making.' Intelligent, prescient, eloquent, Rambo's tethering of poems compels us to inherit its manifold, exquisitely wrought linguistic ravishments, its vision."--Lisa Russ Spaar.